Dissociation between the clinical course and chest imaging in severe COVID-19 pneumonia: A series of five cases - Basille, Damien; Auquier, Marie-Anne; Andréjak, Claire; Rodenstein, Daniel Oscar; Mahjoub, Yazine; Jounieaux, Vincent (Heart & lung, 2021)
•Radiographic and clinical course can diverge in a number of Covid-19 patients.•Hypoxemia during Covid-19 is not only imputable to lung parenchyma lesions.•Covid-19 induces vascular disorders that may result in an intrapulmonary shunt. Although an RT-PCR test is the “gold standard” tool for diagnosing an infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), chest imaging can be used to support a diagnosis of coronavirus disease 2019 (COVID-19) – albeit with fairly low specificity. However, if the chest imaging findings do not faithfully reflect the patient's clinical course, one can question the rationale for relying on these imaging data in the diagnosis of COVID-19. To compare clinical courses with changes over time in chest imaging findings among patients admitted to an ICU for severe COVID-19 pneumonia. We retrospectively reviewed the medical charts of all adult patients admitted to our intensive care unit (ICU) between March 1, 2020, and April 15, 2020, for a severe COVID-19 lung infection and who had a positive RT-PCR test. Changes in clinical, laboratory and radiological variables were compared, and patients with discordant changes over time (e.g. a clinical improvement with stable or worse radiological findings) were analyzed further. Of the 46 included patients, 5 showed an improvement in their clinical status but not in their chest imaging findings. On admission to the ICU, three of the five were mechanically ventilated and the two others received high-flow oxygen therapy or a non-rebreather mask. Even though the five patients’ radiological findings worsened or remained stable, the mean ± standard deviation partial pressure of arterial oxygen to the fraction of inspired oxygen (PaO2:FiO2) ratio increased significantly in all cases (from 113.2 ± 59.7 mmHg at admission to 259.8 ± 59.7 mmHg at a follow-up evaluation; p=0.043). Our results suggest that in cases of clinical improvement with worsened or stable chest imaging variables, the PaO2:FiO2 ratio might be a good marker of the resolution of COVID-19-specific pulmonary vascular insult.